Unveiling the Power of Green Marketing: How Green Advertising and Green Branding Shape Green Buying Behavior – A Case Study on Le Minerale Consumers - Wibowo, Muhammad Firsdo Guntur; Yoestini, Yoestini (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the influence of Green Advertising, Green Branding, and Green Marketing on Green Buying Behavior of Le Minerale Drinking Water consumers in Semarang City. This study is based on the phenomenon of increasing consumer awareness of environmentally friendly products and the importance of green marketing strategies for companies. Data were collected through questionnaires from 100 respondents, who were Le Minerale consumers in Semarang City, and analyzed using the Structural Equation Modeling (SEM) technique with the Partial Least Square (PLS) approach. The results showed that Green Advertising had a positive and significant influence on Green Buying Behavior, while its influence on Green Marketing was not significant. Furthermore, Green Branding was found to have no significant effect on Green Buying Behavior, but had a significant effect on Green Marketing. Green Marketing was proven to have a positive and significant influence on Green Buying Behavior, which indicates that green marketing strategies are effective in encouraging consumer green purchasing behavior. This study also found that Green Marketing can mediate the relationship between Green Advertising and Green Buying Behavior, indicating that green advertising will be more effective if supported by a strong green marketing strategy. The limitations of this study include limited sample coverage, research variables that do not cover all factors that may influence Green Buying Behavior, and data collection methods that only use questionnaires. Further research is suggested to expand the research area, add other variables, and use mixed data collection methods for more comprehensive results.